2021
DOI: 10.1088/1742-6596/1912/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Austenitic ODS 316L Stainless Steel with Arc Plasma Sintering Method

Abstract: Austenitic ODS (Oxide Dispersion Strengthened) 316L steel was fabricated using 316L SS (Stainless Steel) pre-alloyed powder and yttria powders by mechanical milling with APS (Arc Plasma Sintering) method. The powders were milled in High Milling Shaker at 1000 rpm in rotational speed for 10 hours at 10 BPR (Ball Powder Ratio). As milled powders were pressed at 20 Ton and sintered with APS for 0 to 12 minutes at 70 A. The samples were analysed using X-Ray Diffraction (XRD), Microscope Optic (MO) with micro-hardn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…At previous work [27][16] the duration of sintering (means the power of sintering) also contributed to the densification of the samples. It can be concluded that the duration of sintering and the current of sintering also affect densification.…”
Section: Resultsmentioning
confidence: 99%
“…At previous work [27][16] the duration of sintering (means the power of sintering) also contributed to the densification of the samples. It can be concluded that the duration of sintering and the current of sintering also affect densification.…”
Section: Resultsmentioning
confidence: 99%
“…Related to austenitic steel type, 316L stainless steel due to the excellent mechanical, irradiation, and corrosion resistance properties is widely used as a structural material in nuclear power plants [13]. Recently, due to high performance of 316L stainless steel at elevated temperature development of 316L ODS steel is embarking developed [14][15][16]. However, development of 316L ODS steel with additional element to improve performance of the material at elevated temperature is limited.…”
Section: Introductionmentioning
confidence: 99%